2017
DOI: 10.9790/2380-1002027580
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Studies of the Immunomodulator Effect of the Propolis Trigona spp. Extract in a Mouse Model

Abstract: Propolis helps boost the immune system naturally because propolis is rich in bioactive compounds and can help increase the production and activity of immune cells. This product has attracted the interest of researchers in recent decades because of the properties of biological and pharmacological, among others such as antimicrobial, antitumor, anti-inflammatory, antioxidant and immunomodulatory. One of bee species that potentially produce propolis in Indonesia is a local bee species Trigona spp. This study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
(29 reference statements)
2
8
0
1
Order By: Relevance
“…. This study also found that propolis increased NO production in macrophages [36] . The compound in propolis of Trigona sp.…”
Section: Immunomodulatory Effects On Neutrophils Monocytes and Macrosupporting
confidence: 66%
See 1 more Smart Citation
“…. This study also found that propolis increased NO production in macrophages [36] . The compound in propolis of Trigona sp.…”
Section: Immunomodulatory Effects On Neutrophils Monocytes and Macrosupporting
confidence: 66%
“…Two propolis components used in this experiment, caffeic acid and quercetin, had no effect on antibody production, which can be explained by the synergetic effect of the propolis components as a whole [66] . Similarly, Kalsum et al [36] showed that extracts of propolis [37] considered the possibility that limonene, one of the most important constituents in propolis of Trigona sp.…”
Section: Immunomodulatory Effects On the Function Of T And B Lymphocymentioning
confidence: 99%
“…Also, the data of the current work revealed that Treatment of Fusarium toxin-fed mice with PNPs (50, 200 and 400 µg/mL) for 14 days caused a statically significant rise in the number of cells from thymus, spleen, mesenteric lymph nodes and bone marrow compared with Fusarium toxin-fed mice although Fusarium toxin-fed mice treated with PNPs did not cause any significant effect on the number of cells from the PLN. The data of this study are agreed with the data of Gao et al, (2014) that indicated that propolis improved immune function in aged mice and had a direct regulatory effect on basic functional properties of immune cells as a result of its analytical components of polyphenols, flavonoids, cinnamic acid and artepillin-C. Kalsum et al, (2017) proved that terpenoid is one of the essential ingredients in bee glue increase bone marrow cellularity.…”
Section: Discussionsupporting
confidence: 90%
“…The beneficial effect of propolis may be related to its bioactive compounds such as aromatic acids, flavonoids, terpenoids, alkaloids, and polyphenols due to their immunomodulatory properties (Raphael and Kuttan, 2003). Therefore, the role of bioactive compounds in the immunological system may be explained by the fact that the EEP is able to activate macrophages, providing a first line of defense against microorganisms, promote the production of antibodies, and boost the immune response (Raphael and Kuttan, 2003;Kalsum et al 2017). Therefore, our results indicate that propolis has an immunostimulatory potential for broiler breeders.…”
Section: Discussionmentioning
confidence: 99%